Analyzing the Effect of Customer Experience on Customer Loyalty at Floor Coffee Shop - Wan Lukman Fauza; Dwi Astuti (International Journal of Management Science and Information Technology, 2026)
This study aims to examine the effect of customer experience on customer loyalty at Floor Coffee Shop in Bengkalis Regency, Indonesia. A quantitative research method with an associative approach was employed to investigate the relationship between the two variables. Data were collected through questionnaires distributed to 100 customers of Floor Coffee Shop who were selected using a purposive sampling technique, with the sample size determined using the Lemeshow formula. The research instrument was confirmed to be valid and reliable. The collected data were analyzed using descriptive statistics, classical assumption tests, simple linear regression, correlation analysis, the coefficient of determination, and the partial t-test with the assistance of SPSS software. The results indicate that customer experience has a positive and significant effect on customer loyalty. A favorable customer experience, reflected through effective touchpoints, an appropriate service context, and high-quality experiences, enhances customer loyalty by encouraging repeat purchases, positive word-of-mouth recommendations, and long-term commitment to Floor Coffee Shop. These findings suggest that improving customer experience is essential for strengthening customer loyalty and maintaining sustainable business competitiveness. Therefore, the management of Floor Coffee Shop should continuously enhance service quality, create a comfortable atmosphere, and provide adequate facilities to foster long-term customer relationships.